Generation and characterization of a tamoxifen‐inducible EomesCreER mouse line. Issue 10 (30th August 2013) - Pimeisl, Inga‐Marie; Tanriver, Yakup; Daza, Ray A.; Vauti, Franz; Hevner, Robert F.; Arnold, Hans‐Henning; Arnold, Sebastian J.
<x xml:space="preserve">Abstract</x> Transgenic mouse lines expressing inducible forms of Cre‐recombinase in a tissue‐specific manner are powerful genetic tools for studying aspects of development and various processes in the adult. The T‐box transcription factor eomesodermin (Eomes) plays critical roles for maintenance and differentiation of different pools of stem and progenitor cells from early embryonic stages to adulthood. These include trophoblast stem cells, epiblast cells during the generation of the primary germ layers, neurogenic intermediate progenitor cells in embryonic and adult cortical neurogenesis, and maturing natural killer and T cells. Here, we report on the generation and analysis of an EomesCreER‐targeted allele by placing the tamoxifen‐activatable Cre‐recombinase (CreER) under the control of the Eomes genomic locus. We demonstrate that CreER expression recapitulates endogenous Eomes transcription within different progenitor cell populations. Tamoxifen administration specifically labels Eomes‐expressing cells and their progeny as demonstrated by crossing EomesCreER animals to different Cre‐inducible reporter strains. In summary, this novel EomesCreER allele can be used as elegant genetic tool that allows to follow the fate of Eomes‐positive cells and to genetically manipulate them in a temporal specific manner. genesis 51:725–733. © 2013 Wiley Periodicals, Inc.